A meditação mediada por tecnologia como ferramenta de melhoria do estresse no trabalho dos professores - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The present dissertation project aims to analyze meditation as a tool for reducing work stress among teachers. To this end, we conducted two studies presented in the format of independent papers. The first study is a Systematic Literature Review (SLR) on the Contributions of Meditation to Reducing Work Stress among Teachers. Overall, through the SLR, the studies indicate that individuals who apply meditation to some extent in their daily lives achieve positive results in reducing work stress. Additionally, there is a perceived need for more studies and research on this topic, as scarce work addressing the theme was found in Brazil. The second study was quantitative and divided into two periods: Time 01 (before meditation practice) and Time 02 (after meditation practice). A total of 21 teachers participated in the study, responding to both Time 01 and Time 02 measures. Teachers initially responded to the Subjective Well-Being Scale and the Work Stress Scale (Time 01). They then participated in three guided meditation sessions per week, mediated by technology, over a 15-day interval. Afterward, they responded to the same measures as in Time 01. It was found that meditation reduced negative affect indices as well as stress indices, with no effects on positive effects. Therefore, despite the small number of participants and the short practice period, it was possible to identify the positive role of meditation in reducing work stress.
Meditation as a tool for improving work stress among teachers
Keywords: Ambiente de Trabalho; Bem-estar; Estresse; Meditação; Professores; Work Environment; Well-being; Stress; Meditation; Teachers; CIENCIAS HUMANAS::EDUCACAO; ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL